2016
DOI: 10.1038/modpathol.2016.104
|View full text |Cite
|
Sign up to set email alerts
|

Combined comparative genomic hybridization and single-nucleotide polymorphism array detects cryptic chromosomal lesions in both myelodysplastic syndromes and cytopenias of undetermined significance

Abstract: The diagnosis of myelodysplastic syndrome (MDS) can be challenging, and may be facilitated by correlation with cytogenetic testing. Microarray analysis using comparative genomic hybridization and/or single-nucleotide polymorphism array can detect chromosomal abnormalities not seen by standard metaphase cytogenetics. We examined the ability of combined comparative genomic hybridization and single-nucleotide polymorphism analysis (hereafter referred to as 'combined array') to detect changes among 83 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
(75 reference statements)
1
13
0
Order By: Relevance
“…The investigation and definition of smaller lesions that might be involved in disease predisposition should include large cohort of patients that enable the identification of recurrent lesions,22 24 but it is out of the scope of our study. Evans and colleagues20 have recently described an elegant study in which they report all SNP-A lesions defined as deletions and gains >250 kb and UPD >5 Mb in 18 normal bone marrow controls and 83 patients with unexplained cytopenias undergoing pathological evaluation for MDS; the authors have also validated the new lesions using FISH analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation and definition of smaller lesions that might be involved in disease predisposition should include large cohort of patients that enable the identification of recurrent lesions,22 24 but it is out of the scope of our study. Evans and colleagues20 have recently described an elegant study in which they report all SNP-A lesions defined as deletions and gains >250 kb and UPD >5 Mb in 18 normal bone marrow controls and 83 patients with unexplained cytopenias undergoing pathological evaluation for MDS; the authors have also validated the new lesions using FISH analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptic array findings among those patients comprised large-scale UPD (up to 118 Mb) and genomic deletion of loci implicated in MDS pathogenesis (eg, TET2 (4q22) and NUP98 (11p15)). The latent chromosomal lesions revealed by SNP-A helped to indicate clonal hematopoiesis and prompted classification as CCUS 41 . Hence microarray analysis significantly improves the detection rate of clinically significant findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases had cnLOH, including the TET2 locus in two cases. Evans et al () showed that 42% of cases with indeterminate morphological findings could be reclassified as clonal cytopenia of undetermined significance. In AA, the presence of mutations in genes that are known to be involved in myeloid malignancies seems to be associated with reduced survival (Bejar, ).…”
Section: Aberrations Detected Only By Acgh In the Confirmed Mds Casesmentioning
confidence: 99%